Local Shrimp Commodity as an Alternative Supplementary Food Ingredients for Stunting-Free Generation - Dewi Setya Paramitha; Muhammad Sabran; Muhammad Afif Rahman; Raudhatuz Zahra; Radha Rizkita Isnaini; Nurma Nurma; Salsabilla Zulfa; Amalia Solehah; Uswatun Hasanah; Hikmah Hikmah; Mardiah Mardiah (UMBanjarmasin, 2024)
Stunting is still a growth issue that affects toddlers and is defined by growth that differs from normal. Socioeconomic variables, a mother's diet during pregnancy, and a child or toddler's malnutrition may impact this. Natural resources exist throughout Indonesia's large territory and can be used to supply the nation's population's nutritional requirements. Shrimp is one of Indonesia's marine products. Shrimp have active ingredients that are good for humans. These active substances are crucial for preserving the human body's growth, development, and health. We can utilize shrimp as the main component in dishes that are high in nutrients. Stunting must be prevented and stopped by teaching mothers how to process food. Mothers get the chance to cook healthy extras using ingredients that are available locally. In Simpang Warga Dalam Village, community service was used to complete this project. The technique used is an example of processing shrimp dim sum as a substitute for processed food. The findings demonstrate that the mothers played an active part in the training and were knowledgeable about how to prepare shrimp dim sum. It is believed that if this initiative continues, moms will be able to feed their toddlers healthily at home on their own.